The design of a new oxygenation system for water flowing through a tube - Oprea, Mugurel; Băran, Nicolae; Constantin, Mihaela; Nicolau, Ana-Maria; Dobre, Cătălina; Ibrean, Beatrice (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Due to climate change, stagnant or flowing waters continue to warm, and the content of dissolved oxygen in water decreases, endangering aquatic ecosystems and anthropogenic activities. To improve the water quality, water oxygenation or water aeration are used. This paper presents a system that aims to increase the concentration of the O2 dissolved in water flowing through tubes. The assembly of a helix with orifices through which air is introduced with pressure given by a compressor inside a tube is presented.